Penerapan Metode Pembelajaran Role Playing untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Administrasi Humas dan Keprotokolan di SMKN Mojoagung - Aprilia Puji Rahmawati; Durinda Puspasari (Universitas Negeri Surabaya, 2020)
This study aims to analyze the activities of students and teachers, analyze student learning outcomes, and the activeness of students in class XII OTKP 2 SMKN Mojoagung when applying the role playing learning method in the Public Relations and Protocol subjects. The type of research used is Classroom Action Research (CAR) or Classroom Action Research. The subjects used in this study were 35 students of class XII OTKP 2 SMKN Mojoagung. Data collection techniques used are observation, interviews, and documentation. The research instruments used were observation sheets of student and teacher activities during the application of role playing learning methods, student activity observation sheets, and objective tests (pretest and posttest). The results showed that the score of teacher activity in learning increased from cycle I, cycle II and cycle III. The first cycle the score obtained was 2,42. The second cycle increased to 3,5. The third cycle increased again by 4,2. Whereas in student activities in learning there is a score obtained in cycle I is 2,14. Experience an increase in the second cycle which is 3,14. And in cycle III successfully increased to 4,14. Student learning outcomes in learning has increased from cycle I, cycle II and cycle III, where in the first cycle the average results of pretest 54,3 and 65,7 posttest. The second cycle the average results of pretest 68,1 and 70,1 posttest. Then in cycle III the results of the average pretest 83,4 and posttest 90,2. Whereas the activeness of students obtained a score in the first cycle of 38,12%, the second cycle increased to 63%, then in the third cycle to 81,8%.